2013
DOI: 10.4028/www.scientific.net/msf.773-774.573
|View full text |Cite
|
Sign up to set email alerts
|

Laser Cladding of Stainless Steel Substrates with Stellite 6

Abstract: Stellite 6 coatings were produced using laser cladding of two different steel substrates (martensitic and austenitic stainless steels). The chemical composition and microstructure of these coatings were characterized by atomic absorption spectroscopy, optical microscopy and scanning electron microscopy. The microhardness of the coatings was measured and the wear mechanism of the coatings was examined using a pin-on-plate (reciprocating) wear testing machine. The results showed less cracking and pore developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…For deposits produced at 1 kW, the weight loss increased by a factor of about 6 with increasing test load up to 5 kg, but for the higher heat input the rate of weight loss strongly increased by a factor of about 8 with increasing load. It is likely that the greater incidence of microcracks and porosity observed after wear testing of MSS-1.8 samples is due in part to the substrate, being softer and less rigid [9].…”
Section: Discussionmentioning
confidence: 99%
“…For deposits produced at 1 kW, the weight loss increased by a factor of about 6 with increasing test load up to 5 kg, but for the higher heat input the rate of weight loss strongly increased by a factor of about 8 with increasing load. It is likely that the greater incidence of microcracks and porosity observed after wear testing of MSS-1.8 samples is due in part to the substrate, being softer and less rigid [9].…”
Section: Discussionmentioning
confidence: 99%
“…The interdendritic region had a hypoeutectic structure having Ni-based solid solution as the primary phase. Kusmoko et al [78] used LC to deposit Stellite-6 on two substrates, namely austenitic and martensitic stainless steels. Their results indicated that the cladding of martensitic stainless steel produced coatings with fewer defects such as cracks and pores.…”
Section: Lc Of Co-based or Ni-based Alloys On Stainless Steelmentioning
confidence: 99%
“…2, have evidently conferred very high wear resistance to the coatings despite differences in laser power. The high HAZ hardness could, however, degrade resistance to impact loading because of the brittleness of the martensitic HAZ and residual stresses near the coating interface [5].…”
Section: Solid State Phenomena Vol 263mentioning
confidence: 99%